Soft Skills-Based Curriculum Implementation: a Response to Educational Challenges in the Vuca and Tuna Era - Hasan, Dedy Haryadi; Almuhajir, Almuhajir; Ilyas, Mukhlisuddin (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
In the context of rapid global transformation conditions marked by volatility, uncertainty, complexity, and ambiguity (VUCA), with turbulence, uncertainty, novelty, and ambiguity (TUNA), conventional education systems are progressively insufficient in equipping students for future problems. This study examines the deployment of syllabuses focused on soft skills as a strategic response to educational disruptions. This research examines the integration of soft skills—namely communication, critical thinking, adaptability, and emotional intelligence—into curriculum design, pedagogy, and evaluation using qualitative case studies from various geopolitical contexts. The findings indicate that incorporating soft skills cultivates learner resilience, improves collaborative problem-solving, and provides students with competences necessary for addressing the evolving challenges of the 21st century. The study emphasises that policy implications, curriculum, and institutional support are essential elements affecting successful implementation. The research proposes a transformative educational approach that aligns curriculum development with the requirements of the VUCA-TUNA environment, emphasising human-centred, future-ready learning.